Ways of development of the media industry in the conditions of digitalization of the economy - Kosenko, S. A.; Pererva, P. G. (Вінницький національний технічний університет, 2023)
The report explores the features of the development of the media industry under the influence of the processes of global digital transformation. The main trends of modern digital development that affect the media industry of Ukraine are determined.
Шляхи розвитку медіаіндустрії в умовах цифровізації економіки
Keywords: digitalization; society; content; media product; media advertising